(untitled) (Practitioner Research, 2022)
Mastery of the Physics concept and the ability to apply this knowledge in everyday life can contribute to the development of the country. However, the skills of secondary school students in physics subject are less impressive. The fact is that learning experience in the classroom, also known as conventional learning, leaves a meaningful impression on students. Thus, a study on the topic of Forces and Motion – Forces in Equilibrium was conducted on Form Four students at a secondary school in the Northern Peninsular Malaysia. Qualitative data through in-depth semi-structured interviews were conducted on four students from the experimental group. The main purpose of the study was to explore students’ opinion on learning physics by using conventional method as opposed to learn physics using PhET Simulation supported by MoPSIF Module. Thematic analysis from the interview found that the characteristics of students who learned physics via conventional method were lack of interest, boredom, not actively engaging in group activities, less friendly teacher-student interactions, and limited to reference books and textbooks for self-learning. On the other hand, learning physics using PhET Simulation and MoPSIF Module had a positive impact on students’ interest and motivation, the pleasure of studying as a group or self-learning, help to study for exams, and suitable as a method of learning physics for home-based teaching and learning. It is recommended that PhET Simulation supported by MoPSIF Module be used to enhance students’ learning in physics subject especially during pandemic.